A framework for strategic planning of spatially cumulated green roofs to reduce urban heat - Case study of Wuppertal, Germany - Jana Brenner; Jochen Hack (Urban Forestry & Urban Greening, 2026)

Neighbour perspectives on cultural ecosystem services of blue-green infrastructures: The ecovillage Hannover, Germany - Andrea Nóblega-Carriquiry; Hug March; David Sauri; Jochen Hack (Ecosystem Services, 2025)

An urban rivers renaissance? Stream restoration and green–blue infrastructure in Latin America – Insights from urban planning in Colombia - Gonzalo Pradilla; Jochen Hack (Urban Ecosystems, 2024)
While urban river restoration has become mainstream in the Global North, it remains scarce in Latin America, where most literature focuses on water quality, stream habitats, and watershed assessment, but planning and implementation lag behind. Colombia is undergoing a paradigm shift after pioneering the integration of green and blue infrastructure (GBI) into urban planning in the early 2000s (namely Estructura Ecológica Principal ). A surge in river renaturalization initiatives is underway, with large and intermediate cities planning and executing projects. We systematically assessed the integration of rivers and GBI into local policies ( Planes de Ordenamiento Territorial ) and found widespread and strong recognition of streams, wetlands, and ecosystem services in urban planning, higher than previously reported. Most cities emphasize river multifunctionality, ecological connectivity, public space, and recreation, as well as disaster risk reduction, advancing toward sustainable urban water and drainage systems. However, significant gaps persist regarding climate change resilience, participation, and social justice. In a region marked by high inequality, pre-existing spatial exclusion could be amplified by urban renewal, greening, and tourism due to unfair resettlement conditions and gentrification. Such trade-offs can undermine the ecological and social benefits of restoration. We highlight the crucial role of civil society and grassroots activism in protecting and defending urban commons and conclude by recommending a critical examination of GBI and river restoration efforts in Latin America. Colombia’s case can serve as both a reference and a cautionary tale for other cities in the region to achieve outcomes that promote equity and justice amid pressing social and environmental challenges.

Multi-criteria site selection and hydraulic modeling of green flood retention measures in a highly urbanized basin in Costa Rica - Carolina Lopes Monteiro; José Ricardo Bonilla Brenes; Alberto Serrano-Pacheco; Jochen Hack (Urban Forestry & Urban Greening, 2023)

Correction to: Development and modelling of realistic retrofitted Nature-based Solution scenarios to reduce flood occurrence at the catchment scale - Valerie Chen; Jose Ricardo Bonilla Brenes; Fernando Chapa; Jochen Hack (Ambio, 2022)
In the original publication, the affiliation of all the authors were mixed up and processed incorrectly. It has been updated in this correction.

Planning and governing nature-based solutions in river landscapes: Concepts, cases, and insights - Christian Albert; Jochen Hack; Stefan Schmidt; Barbara Schröter (Ambio, 2021)
Nature-based solutions (NBS), understood as actions that use ecosystem processes to address societal needs, can play important roles to future-proof river landscape development for people and nature. However, knowledge gaps exist how NBS can be planned and implemented at landscape scales. This Special Issue brings together insights and experiences from studies of assessing, planning, and implementing NBS in river landscapes in Europe and beyond. It addresses three research fields: (i) NBS effects, looking at the effectiveness of NBS to achieve ecological, social, and/or economic outcomes, (ii) NBS planning, focusing on approaches for planning and designing NBS, and (iii) NBS governance, relating to governance and business models for implementation. The twelve contributions deliver evidence on how NBS outperform conventional, rather technical solutions, provide guidance and tools to operationalize the NBS concept into practice, and showcase successful governance models of NBS in different contexts. The editorial ends with an outlook on further research needs.

Co-design of experimental nature-based solutions for decentralized dry-weather runoff treatment retrofitted in a densely urbanized area in Central America - Maria Pérez Rubi; Jochen Hack (Ambio, 2021)
The quality of water in many urban rivers in Latin America is increasingly degrading due to wastewater and runoff discharges from urban sprawl. Due to deficits in sanitary drainage systems, greywater is discharged to the stormwater drainage network generating a continuous dry-weather runoff that reaches rivers without treatment. One of the main challenges in the region is to achieve sustainable management of urban runoff for the recovery of rivers ecosystem integrity. However, retrofitting conventional centralized wastewater drainage networks into the existing urban grid represents important social, economic and technical challenges. This paper presents an alternative adaptive methodology for the design of Nature-based Solutions for decentralized urban runoff treatment. Through this study, technical solutions commonly used for stormwater management were adapted for dry-weather runoff treatment and co-designed for the particular conditions of a representative study area, considering space availability as the main constraining factor for retrofitting in urban areas. The application of a co-design process in a dense neighbourhood of the Great Metropolitan area of Costa Rica brought to light valuable insights about conditions that could be hindering the implementation of NBS infrastructures in Latin America.

Development and modelling of realistic retrofitted Nature-based Solution scenarios to reduce flood occurrence at the catchment scale - Valerie Chen; Jose Ricardo Bonilla Brenes; Fernando Chapa; Jochen Hack (Ambio, 2021)
Decentralized Nature-based Solutions such as Urban Green Infrastructures (UGI) are increasingly promoted to reduce flooding in urban areas. Many studies have shown the effectiveness of flood control of UGI at a plot or neighbourhood level. Modelling approaches that extrapolate their flood reducing impact to larger catchment scales are often based on a simplistic assumption of different percentages of UGI implementation. Additionally, such approaches typically do not consider the suitable space for UGI and potential implementation constraints. This study proposes a scenario development and modelling approach for a more realistic upscaling of UGI based on empirical insights from a representative neighbourhood. The results from this study, conducted in the metropolitan area of Costa Rica, show that upscaling the full potential for UGI could significantly reduce surface runoff, peak flows, and flood volumes. In particular, the permeable pavement has the highest potential for flood reducing in public space while cisterns perform best at the property level. These results can guide the formation of policies that promote UGI.

Education in Ecological Engineering—a Need Whose Time Has Come - Glenn Dale; Gabriela Dotro; Puneet Srivastava; David Austin; Stacy Hutchinson; Peter Head; Ashantha Goonetilleke; Alexandros Stefanakis; Ranka Junge; José A. Fernández L.; Vanessa Weyer; Wayne Truter; et al. (Circular Economy and Sustainability, 2021)
Overcoming Limitations of Ecology and Engineering in Addressing Society’s Challenges By providing an integrated, systems-approach to problem-solving that incorporates ecological principles in engineering design, ecological engineering addresses, many of the limitations of Ecology and Engineering needed to work out how people and nature can beneficially coexist on planet Earth. Despite its origins in the 1950s, ecological engineering remains a niche discipline, while at the same time, there has never been a greater need to combine the rigour of engineering and science with the systems-approach of ecology for pro-active management of Earth’s biodiversity and environmental life-support systems. Broad consensus on the scope and defining elements of ecological engineering and development of a globally consistent ecological engineering curriculum are key pillars to mainstream recognition of the discipline and practice of ecological engineering. The Importance of Ecological Engineering in Society In this paper, the importance of ecological engineering education is discussed in relation to the perceived need of our society to address global challenges of sustainable development. The perceived needs of industry, practitioners, educators and students for skills in ecological engineering are also discussed. The Importance and Need for Ecological Engineering Education The need for integrative, interdisciplinary education is discussed in relation to the scope of ecology, engineering and the unique role of ecological engineering. Scope for a Universally Recognised Curriculum in Ecological Engineering The scope for a universally recognised curriculum in ecological engineering is presented. The curriculum recognises a set of overarching principles and concepts that unite multiple application areas of ecological engineering practice. The integrative, systems-based approach of ecological engineering distinguishes it from the trend toward narrow specialisation in education. It is argued that the systems approach to conceptualising problems of design incorporating ecological principles is a central tenant of ecological engineering practice. Challenges to Wider Adoption of Ecological Engineering and Opportunities to Increase Adoption Challenges and structural barriers to wider adoption of ecological engineering principles, embedded in our society’s reliance on technological solutions to environmental problems, are discussed along with opportunities to increase adoption of ecological engineering practice. It is suggested that unifying the numerous specialist activity areas and applications of ecological engineering under an umbrella encompassing a set of core principles, approaches, tools and way of thinking is required to distinguish ecological engineering from other engineering disciplines and scale up implementation of the discipline. It is concluded that these challenges can only be realised if ecological engineering moves beyond application by a relatively small band of enthusiastic practitioners, learning by doing, to the education of future cohorts of students who will become tomorrow’s engineers, project managers, procurement officers and decision makers, applying principles informed by a growing body of theory and knowledge generated by an active research community, a need whose time has come, if we are to deploy all tools at our disposal toward addressing the grand challenge of creating a sustainable future.

Cost-Effective Optimization of Nature-Based Solutions for Reducing Urban Floods Considering Limited Space Availability - Apoorva Singh; Arup Kumar Sarma; Jochen Hack (Environmental Processes, 2020)